Pansclerotic Morphea Following COVID-19: A Case Report and Review of Literature on Rheumatologic and Non-rheumatologic Dermatologic Immune-Mediated Disorders Induced by SARS-CoV-2 - Lotfi, Zahra; Haghighi, Anousheh; Akbarzadehpasha, Amirhossein; Mozafarpoor, Samaneh; Goodarzi, Azadeh (Frontiers in Medicine, 2021)
While mucocutaneous manifestations of COVID-19 have been frequently reported and added to our knowledge every day during the pandemic, another issue is the COVID-related diseases that can present as intensified lesions of underlying diseases, a new disease, or changes in the behavior of an old lesion. Given that immune system overreaction and cytokine storm are among the most prominent events in COVID-19, the incidence of autoimmune diseases is expected to increase after COVID-19, as confirmed in several reports. To increase the body of knowledge about short- and long-term outcomes of COVID-19 for specialists, it is essential that similar cases be reported and collected for years to come. The present study investigated a case of pansclerotic morphea that rapidly progressed a few weeks after infection with COVID-19 in a 57-year-old woman with no history of any autoimmune skin or rheumatic diseases. She was prescribed outpatient COVID-19 treatment of azithromycin, vitamins D and C, and then quarantined for 2 weeks. The manifestations of the disease were exacerbated at each follow-up and sampling visit at short intervals. This kind of pansclerotic morphea is reported for the first time.